Effect of bovine viral diarrhea virus on subsequent infectivity of bovine gammaherpesvirus 4 in endometrial cells in primary culture: An in vitro model of viral co-infection - Romeo, Florencia (2021)
Bovine viral diarrhea virus (BVDV) and bovine gammaherpesvirus 4 (BoHV-4) infect the uterus of cattle, being responsible for huge economic losses. Most of the pathogenesis of BoHV-4 in the bovine reproductive tract has been elucidated by conducting tests on primary cultures. Thus, it is important to have optimal in vitro conditions, avoiding the presence of other pathogens that can alter the results. BVDV is one of the most frequent viral contaminants of cell cultures. Considering that non-cytopathic (NCP) BVDV biotype can generate persistently infected (PI) cattle, which are the major source for virus transmission in susceptible herds, it is important to check products derived from cattle that are intended to be used in research laboratories. The aim of this work was to evaluate how the natural infection of bovine endometrial cells (BEC) with a NCP BVDV strain (BEC + BVDV) affects BoHV-4 replication. We have demonstrated a delay in BoHV-4 gene expression and a decrease in viral load in the extracellular environment in BEC + BDVD cells compared to BEC (BVDV-free) cells. These results confirm that replication of BoHV-4 in BEC primary cultures is affected by previous infection with BVDV. This finding highlights the importance of ruling out BVDV infection in bovine primary cell cultures to avoid biological interference or misinterpretation of results at the time of performing in vitro studies with BoHV-4.